2005
DOI: 10.1063/1.1862326
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity due to current redistribution in the Hall effect of semiconductor-metal hybrid structures

Abstract: Experimental and theoretical studies have shown that nonmagnetic semiconductor-metal hybrid structures can exhibit a very large magnetoresistance effect, the so-called extraordinary magnetoresistance (EMR) effect. The EMR can be useful in magnetic-field sensors and read heads. We show that the sensitivity of a linear hybrid structure can be further enlarged by using an optimized configuration of current leads and voltage probes. Strikingly, we find that the EMR and the Hall effect cooperate and thereby improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…This is in a qualitative agreement with the MR eect magnitude in the IU IU FEM calculations (Fig. 3) as well as with earlier conclusions [6,8,9]. It results from the FEM analysis that the large magnitude of the EMR eect and the change of its sign with the magnetic eld polarization for the IU IU conguration is the eect of interference of the MR and Hall eects in the SM heterostructure.…”
Section: Investigation Of Emr Eectsupporting
confidence: 79%
See 1 more Smart Citation
“…This is in a qualitative agreement with the MR eect magnitude in the IU IU FEM calculations (Fig. 3) as well as with earlier conclusions [6,8,9]. It results from the FEM analysis that the large magnitude of the EMR eect and the change of its sign with the magnetic eld polarization for the IU IU conguration is the eect of interference of the MR and Hall eects in the SM heterostructure.…”
Section: Investigation Of Emr Eectsupporting
confidence: 79%
“…The FEM calculations (Fig. 3 top) do not revealed such asymmetry which is also conrmed in literature [3,7,8,9], however some experimental data [4] did reveal the existence of such asymmetry. However, the experimentally observed asymmetry was very small.…”
Section: Investigation Of Emr Eectsupporting
confidence: 56%
“…In a symmetric IVVI contact configuration the resultant resistance is symmetrical with applied magnetic field, where the same resistance value is obtained for a positive or negative magnetic field of the same magnitude. The first thing to notice about the asymmetric IVVI contact configuration is that the resultant plot of resistance against applied magnetic field is also asymmetric 17,18,20,87,92 . This can be observed in Figure 4.7.…”
Section: Previous Geometrical Resultsmentioning
confidence: 99%
“…Investigations into the VIVI contact configuration have also been reported. Here, only one voltage probe is located between the two current contacts 17,18,92,94 . In this configuration the magnetoresistance is also asymmetric with magnetic field 92 .…”
Section: Previous Geometrical Resultsmentioning
confidence: 99%
“…It has been shown that slightly enhanced low-field sensitivity can be obtained with an asymmetric electrode arrangement. 10,11 In this work, we describe a device with a 3-contact configuration, which combines the EMR effect and the Hall effect. The Hall effect has a linear response to a magnetic field change producing a considerable sensitivity in the low-field region.…”
mentioning
confidence: 99%